Contribuições do Pibid para a formação inicial de professores : a terceira margem do rio - Gonzatti, Sônia Elisa Marchi (2015)
This study focuses on the main contributions of the Institutional Scholarship Program for Teaching Initiation (PIBID) to qualify teachers‟ initial education from an innovation educational perspective. Innovation is conceived from a theoretical and epistemological perception presuming tension and ruptures of principles supporting prevailing education models. Such approach was chosen since PIBID is an innovative program, which aims to tension educational teaching models and enhance the interaction between university and school. The theoretical-methodological investigation attempted to discuss teaching initiation as innovative proposal in the context of teachers‟ education. Regarding to methodology, a case study was carried out as an interdisciplinary subproject of PIBID in a Community Institution of Higher Education of Rio Grande do Sul. Data was collected through interviews and observations with the scholarship teamwork in three partner schools. Aiming at discussing educational innovation in the program, two study approaches were developed. The first one aimed to reflect on the contributions of PIBID regarding the models of teaching education. Reconsidering connection between theory and practice and the interdisciplinary perspective and the school as a learning teaching environment are empirical highlighted aspects that indicate ruptures and innovation regarding such models. The second study approach aimed to investigate the interaction of PIBID with the school culture. Interdisciplinary practice and epistemological and methodological implications emerge as the main factors that cause tensions and ruptures with the school culture hegemony. Results indicate that teaching initiation as an experience of teacher education reinvention has become an area of confluence and contrast of perspectives, beliefs and conceptions about teaching. Therefore, PIBID – herewith designed as the third bank of the river - has fulfilled its purpose concerning teacher‟s education.